2017
DOI: 10.1155/2017/1756473
|View full text |Cite
|
Sign up to set email alerts
|

The Internet Use for Health Information Seeking among Ghanaian University Students: A Cross-Sectional Study

Abstract: The aim of the study was to investigate university students' use of the Internet for health purpose in the Ghanaian context. The study employed a quantitative cross-sectional design. A total of 650 out of 740 students selected from 3 different universities participated, giving a response rate of 87.7% (650/740). Data were obtained using questionnaires and frequency and percentages were used to analyze data. The results show that university students are active users of the Internet as 78.3% (509/650) used Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
84
5
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(111 citation statements)
references
References 28 publications
(35 reference statements)
19
84
5
3
Order By: Relevance
“…The Internet is an attractive and common source of health information today [16,28,31]. The use of the internet to access health information has increased in recent years due to the reasons such as accessibility, high volume of information disseminated trough that, confidentiality, low cost, multi-media capabilities and the ability to interact and to gain support [24,27,32]. Reports indicate that adolescents are increasingly spending their time for using internet.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Internet is an attractive and common source of health information today [16,28,31]. The use of the internet to access health information has increased in recent years due to the reasons such as accessibility, high volume of information disseminated trough that, confidentiality, low cost, multi-media capabilities and the ability to interact and to gain support [24,27,32]. Reports indicate that adolescents are increasingly spending their time for using internet.…”
Section: Resultsmentioning
confidence: 99%
“…A study among the Nigerian students has found that only 50% of participants consulted with a physician about their health after searching online health information [38]. A study at 3 Ghanaian universities also reported that 72.4 percent of respondents used retrieved online information as a basis for lifestyles modifications and more than 73 percent of students stated that access to online health information improved or partially improved their health status, while 1.2 percent said that using Internet has no effect on their overall health [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Istraživanja grupe autora iz Gane ukazuju na postojanje značajne povezanosti između onlajn zdravstvene aktivnosti sa jedne i zdravstenog statusa sa druge strane. Osobe koje imaju dijagnostifikovanu hroničnu bolest, osobe sa bolesnim članom porodice i lica sa narušenom zdravstvenom percepcijom češći su konzumenti zdravstvenih informacija na internetu (15). Istraživanje provedeno u Sjedinjenim Američkim Državama utvrdilo je statistički značajno češću onlajn zdravstvenu aktivnost kod osoba koje imaju hroničnu bolest u odnosu na oboljele od akutne bolesti koji su skloniji odabiru izravnije i tačnije informacije, poput pregleda u zdravstvenim ustanovama (16).…”
Section: Diskusijaunclassified
“…Značajniju spremnost za razgovorom sa ljekarom o onlajn zdravstvenim informacijama detektovala su samo istraživanja studentske populacije (Saudijska Arabija 57.3%, Gana 39.5%) (23,24). Kvalitetna komunikacija o onlajn zdravstvenim informacijama zahtijeva razumijevanje potrebe pacijenta za zdravstvenom edukacijom na internetu .…”
Section: Diskusijaunclassified